2015
DOI: 10.1016/j.jcin.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Bioresorbable Scaffold Sizing Using QCA-Dmax and Clinical Outcomes at 1 Year in 1,232 Patients From 3 Study Cohorts (ABSORB Cohort B, ABSORB EXTEND, and ABSORB II)

Abstract: Implantation of an oversized Absorb scaffold in a relatively small vessel appears to be associated with a higher 1-year MACE rate driven by more frequent early MI. (ABSORB Clinical Investigation, Cohort B [ABSORB Cohort B], NCT00856856; ABSORB EXTEND Clinical Investigation [ABSORB EXTEND], NCT01023789; ABSORB II Randomized Controlled Trial [ABSORB II], NCT01425281).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
1
34
2
2
Order By: Relevance
“…Conversely, a recent study also reported that implantation of an oversized bioresorbable scaffold in a relatively small vessel appeared to be associated with a higher 1-year adverse event rate, 36 which is inconsistent with our results with metallic DES. It is reasonable that proper implantation methods may vary according to the design and material of device.…”
Section: Long-term Outcomescontrasting
confidence: 99%
“…Conversely, a recent study also reported that implantation of an oversized bioresorbable scaffold in a relatively small vessel appeared to be associated with a higher 1-year adverse event rate, 36 which is inconsistent with our results with metallic DES. It is reasonable that proper implantation methods may vary according to the design and material of device.…”
Section: Long-term Outcomescontrasting
confidence: 99%
“…The incidence of MI was low, probably due to inclusion of periprocedural events only. In a recent meta-analysis [28] patients treated with BVS implantation had a similar risk of myocardial infarction (OR = 1.36, 95% CI: 0.98–1.89; p = 0.06) and death (OR = 0.95, 95% CI: 0.45–2.00; p = 0.89) but with higher risk of define/probable ScT (OR = 1.99, 95% CI: 1.00–3.98; p = 0.05), especially between 1 and 30 days after implantation (OR = 3.11, 95% CI: 1.24–7.82; p = 0.02) as compared to the metallic stent group [28]. However, Cassese et al did not evaluate target vessel myocardial infarction (TVMI), which was significantly higher for BVS in comparison to conventional stents in data presented in two other meta-analyses [26, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in ABSORB EXTEND, systematic postdilatation did not emerge as a significant treatment modifier . Differently, in an expanded cohort that mostly included patients from ABSORB EXTEND, implantation of an oversized BVS in a relatively small vessel appeared to be associated with a higher 1‐year rate of combined ischemic events, driven by more frequent early MI . In a propensity score matched analysis of BVS and EES, including all patients from ABSORB EXTEND, BVS were associated with comparable rates of TLF and numerically albeit nonsignificantly higher rates of scaffold thrombosis (1.0% vs. 0.3%) compared with EES (Abizaid A, presented at EuroPCR 2015).…”
Section: Multicenter Registriesmentioning
confidence: 83%